Numerical and Experimental Analysis of ) HE10 ( Hydrous Ethanol Blend in a PFI Gasoline Engine - Musaab O. El-Faroug; Salem A. Basher (African Journal of Advanced Pure and Applied Sciences, 2025)
This work examines the effects of 10% hydrous ethanol–gasoline blends (HE10) on the combustion and emission behavior of a spark-ignition port fuel injection (PFI) engine. Numerical simulations using a CFD solver evaluated the role of water content in blends (E0, HE10W3, HE10W5) on in-cylinder pressure, heat release rate, and NOx formation at 1200 rpm and 50 N·m. Experimental tests were also carried out on a four-cylinder PFI gasoline engine at 1800 rpm under different loads to assess the influence of HE10 on particulate matter (PM) and gaseous emissions. The results indicate that hydrous ethanol blends reduce peak in-cylinder pressure and heat release compared with gasoline, mainly due to higher latent heat of vaporization and lower heating value. Nonetheless, HE10 provided clear emission advantages. PM number and mass concentrations declined substantially, with a 64.9% reduction in particulate mass at 30 N·m relative to gasoline, and particle size distributions showed fewer nucleation and accumulation mode particles. In addition, HE10 lowered NOx, HC, CO, and CO₂ emissions. A slight increase in brake-specific fuel consumption was observed, reflecting the lower energy density of hydrous ethanol.